Mandibular Reconstruction with Autogenous Graft After Surgical Treatment of Cemento-Ossifying Fibroma: a Case Report and Literature Review - Alves, Rodrigo Lemos; Gusmão, Jonas Nogueira Ferreira Maciel; Silva, Bruno Frota Amora; Bezerra, Rodrigo Cristhian Avelino; Santos, Eliardo Silveira; Mont’Alverne Lopes Filho, Antonio (Brazilian Journal of Case Reports, 2021)
Fibro-bone lesions (LFO) are defined as a group of lesions characterized by the replacement of normal bone tissue with fibrous connective tissue, of variable cellularity, permeated by a variable amount of mineralized material, whose microscopic appearance may resemble bone, cement or a mixture of both. Among the injuries that make up this group, we can mention: fibrous dysplasia, ossifying fibroma, bone dysplasia and cemento-bone dysplasia. In this case report, we presented a mandibular reconstruction with free autogenous graft from the iliac crest, with the use of stereolithography prototyping, after the surgical treatment of a cemento-ossifying fibroma, as well as to describe the clinical, epidemiological, radiographic characteristics, and histological, the differential diagnosis and the form of treatment of the referred pathology.